Using Chatgpt for Translating Songs Between Bahasa Indonesia and English - Yong H S, David (LINGUISTIK TERAPAN, 2024)
As a first-year PhD student, I was inspired by my lecturers to embark on this research to explore self translation with the aid of AI, specifically ChatGPT by OpenAI. This study investigates the potential benefits and challenges of using AI to translate Christian praise and worship songs between Bahasa Indonesia and English. By focusing on linguistic accuracy, cultural adaptation, and artistic integrity, using a qualitative case study approach, I evaluated the efficacy of ChatGPT in enhancing the quality and efficiency of self translation in worship music. My research involved translating five songs—two from English to Indonesian, two from Indonesian to English, and one from Batak to English—using an iterative process that combined ChatGPT's outputs with Google Translate and human expertise. The findings reveal that while ChatGPT can effectively bridge linguistic gaps and maintain the original compositions' integrity, human involvement remains crucial for ensuring linguistic, cultural, and contextual accuracy. This study underscores the potential of AI as a valuable tool in the self-translation of worship songs, highlighting the importance of human-AI collaboration.